HMGB2 is associated with malignancy and regulates Warburg effect by targeting LDHB and FBP1 in breast cancer - Fu, Deyuan; Li, Jing; Wei, Jinli; Zhang, Zhengquan; Luo, Yulin; Tan, Haosheng; Ren, Chuanli (Cell communication and signaling, 2018)
High-mobility group box 2 (HMGB2) is implicated in tumorigenesis in various cancers. However, the clinical significance of HMGB2 signaling in human breast cancer progression remains unknown. We investigated HMGB2 expression in 185 cases of primary breast cancer and matched normal breast tissue specimens, and explored the underlying mechanisms of altered HMGB2 expression as well as the impact of this altered expression on breast cancer growth and on aerobic glycolysis using in vitro and animal models of breast cancer. HMGB2 was more highly expressed in tumor-cell nuclei of breast cancer cells than in the adjacent normal breast tissues (P < 0.05). Higher HMGB2 expression correlated with larger tumor size (P = 0.003) and advanced tumor stage (P = 0.033). A Cox proportional hazards model revealed that HMGB2 expression was an independent prognostic factor for breast cancer after radical resection (P < 0.05). Experimentally, knockdown of HMGB2 expression by stable transfected shRNA significantly decreased the growth and glycolysis of breast cancer cells both in vitro and in mouse models. Mechanically, promotion of breast cancer progression by HMGB2 directly and significantly correlated with activation of LDHB expression and inactivation of FBP1 expression. These results disclose a novel role for HMGB2 in reprogramming the metabolic process in breast cancer cells by targeting LDHB and FBP1 and provide potential prognostic predictors for breast cancer patients.